Predicting the competitive position of extended gates: the case of inland customs zones - Sherafatipour, Saeid; Saffarzadeh, Mahmoud; Tavasszy, Lóránt; Fatemi Ardestani, S. Farshad (European Journal of Transport and Infrastructure Research, 2018)
The extended gate concept aims to reduce the pressure on international ports by postponing administrative processes from these border gates to inland terminals. At present, this approach is used mainly in the container transport industry in European and Asian ports. In this paper we study an extended gate concept, where inland customs services are made available from all entry points of a country. Our aim is to predict the portion of the current flow through border gates that is diverted to these inland customs zones. We propose a time-series gravity models to predict these changes and estimate the parameters of this model using publicly available data for different cargo groups. The focus of our application is Iran, a nation with a large and emerging economy, where goods currently enter through 26 main border gates. In addition to this flow diversion model we explain how flow matrices can be synthesized from the available transport statistics. Our calculations indicate that transportation cost, travel time and customs tariff discounts are the most important for the choice of customs zone. The attractiveness of extended gates increases as the direct cost of transportation between the border gate and destination province rises. Extended customs zones in Iran would have an average share of import flows in 2025 of around 13% and attract a volume of 8.4 million metric tons of goods.